Liver Disorders that Induced by Burkholderia Mallei and the Role of Phenolic Compounds of Rheum Ribes in Treatment - Ahmed Hamad Saleh (University of Thi-Qar Journal of Science, 2020)
The present study was designed to show the potential role of phenolic compounds against the toxicity of Burkholderia mallei. The study used 30 adult male rats that distributed to five groups (each group consist 6 rats); control group that received normal saline, second group rat injected intraperitoneal with B. mallei at dose 10 6 cell/ ml. third group rat injected intraperitoneal with B. mallei at dose 1 08 cell/ ml. fourth group rat injected intraperitoneal with B. mallei at dose 1 0 6 cell/ ml and treated with 250ug/ml of phenolic compounds for four weeks. Keywords—component, formatting, style, styling, insert (key words). Fifth group rat injected intraperitoneal with B. mallei at dose 1 08 cell/ ml and treated with 250ug/ml of phenolic compounds for four weeks. Sixth group rat treated with 250ug/ml of phenolic compounds for four weeks. The results show high significant increased (P < 0.05) in levels AST, ALT, ALP and MDA with high significant decreased (P < 0.05) in levels GSH, catalase in second and third groups compared with control group. The results of fourth, fifth and sixth groups show non-significant changes (P < 0.05) in all parameters compare with control group when using Rheum ribes. It was concluded that Rheum ribes has been potential role against the toxicity of B. mallei in adult male rats.